2021
DOI: 10.3390/jcm10194519
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Feasibility, and Impact of Enalapril on Cardiorespiratory Physiology and Health in Preterm Infants with Systemic Hypertension and Left Ventricular Diastolic Dysfunction

Abstract: Neonatal hypertension has been increasingly recognized in premature infants with bronchopulmonary dysplasia (BPD); of note, a sub-population of these infants may have impaired left ventricular (LV) diastolic function, warranting timely treatment to minimize long term repercussions. In this case series, enalapril, an angiotensin-converting enzyme (ACE) inhibitor, was started in neonates with systemic hypertension and echocardiography signs of LV diastolic dysfunction. A total of 11 patients were included with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Recent data has also indicated that inferior LV function, in particular diastolic function, may contribute to the pathophysiology of cPH in BPD, through chronic elevation of LV end diastolic pressure and subsequently left atrial and pulmonary venous pressure. (29,30) By reducing systemic afterload, diuretic therapy may also improve LV end diastolic pressure and its contributory effects on pulmonary venous pressure in cPH pathophysiology and pulmonary edema. Our ndings of reduction in DBP and signi cant improvement in LV MPI, a marker of global function, in association with improvement in PVR markers after treatment lend support to this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data has also indicated that inferior LV function, in particular diastolic function, may contribute to the pathophysiology of cPH in BPD, through chronic elevation of LV end diastolic pressure and subsequently left atrial and pulmonary venous pressure. (29,30) By reducing systemic afterload, diuretic therapy may also improve LV end diastolic pressure and its contributory effects on pulmonary venous pressure in cPH pathophysiology and pulmonary edema. Our ndings of reduction in DBP and signi cant improvement in LV MPI, a marker of global function, in association with improvement in PVR markers after treatment lend support to this hypothesis.…”
Section: Discussionmentioning
confidence: 99%